Patient with ovarian insufficiency: baby born after anticancer therapy and re-transplantation of cryopreserved ovarian tissue - Vladimir Isachenko; Bernd Morgenstern; Plamen Todorov; Evgenia Isachenko; Peter Mallmann; Bettina Hanstein; Gohar Rahimi (BMC, 2020)
Abstract Background The second major cause of death is cancer. In fact, the effectiveness of anticancer treatments and positive long-term prognosis for young women has increased. However, the problem of post-cancer infertility plays a significant role, because chemotherapy can be gonadotoxic and lead to the functional death of ovaries. There is potential key solution to this problem: cryopreservation of ovarian tissue before cancer therapy with re-implantation after convalescence. Data regarding cryopreservation and re-transplantation of ovarian tissue from patients with ovarian insufficiency is limited. The aim of this treatment was the re-transplantation of cryopreserved ovarian tissue after anticancer therapy of patient with ovarian insufficiency (56 IU/l FSH, 8 ng/l β-estradiol, < 1.1 ng/ml anti-Mullerian hormone, 1 primary follicle per 10mm3). Case presentation After the operation, four tissue fragments (10-16 × 8-13 × 1.0-1.2 mm) were cooled to 5 °C in the freezing medium (culture medium+ 6% ethylene glycol+ 6% dimethyl sulfoxide+ 0.15 M sucrose) for 24 h, frozen and thawed. Freezing was performed in four standard 5 ml cryo-vials with ice formation at − 9 °C, cooling from − 9 to − 34 °C at a rate of − 0.3 °C/min and plunging at − 34 °C into liquid nitrogen. After thawing in a 100 °C (boiling) water bath, the removal of cryoprotectants was performed in 0.5 M sucrose with 20 min. exposure in sucrose and 30 min. stepping rehydration. After thawing of one cryo-vial, part (5 mm3) of experimental ovarian tissue after 7 day in vitro culture was histological evaluated and two ovarian fragments (8 × 7 × 1.0 mm and 7 × 6 × 1.0 mm) were re-transplanted. The quantity of follicles after cryopreservation and in vitro culture was not increased (P > 0.1): it was found 1 primordial follicle in 5 mm3 of tissue. Thirty seven days after the re-transplantation of ovarian tissue, the restoration of the menstrual cycle of Patient W. was noted. Three months after the transplantation, the patient became spontaneously pregnant and delivered a healthy baby girl at term. Conclusions Described protocol of conventional cryopreservation of ovarian tissue can be used for treatment of patients with ovarian insufficiency.